2010
DOI: 10.5539/mas.v4n9p130
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Plant Regeneration from Leaf Explants of Artemisia vulgaris L. – A Medicinal Herb

Abstract: A reliable protocol for callus induction and regeneration were developed for leaf explants of Artemisia vulgaris L. Percent of callus induction and regeneration were higher in the young leaves. MS medium containing 1.0 mgl -1 BAP and 3.0 mgl -1 NAA is the optimum concentration for induction of callus. So produced callus was subcultured on Murashige -Skoog (MS) medium with 1.0 mgl -1 6-benzylaminopurine (BAP), 3.0 mgl -1 gibberellic acid (GA 3 ) produced the highest mean number of shoots (35.85±0.81) per explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…As in the present study, the reduction of shoot regeneration potential by the combined effect of BAP and GA 3 compared to a medium with cytokinin alone was also demonstrated in Guizotia abyssinica (Baghel and Bansal 2014). On the contrary, a combination of BAP and GA 3 had shown better response in Artimisia vulgaris (Borzabad et al 2010). The shoots developed by BAP over its optimal level (2.5 mg/l) showed stunted growth.…”
Section: Resultsmentioning
confidence: 51%
“…As in the present study, the reduction of shoot regeneration potential by the combined effect of BAP and GA 3 compared to a medium with cytokinin alone was also demonstrated in Guizotia abyssinica (Baghel and Bansal 2014). On the contrary, a combination of BAP and GA 3 had shown better response in Artimisia vulgaris (Borzabad et al 2010). The shoots developed by BAP over its optimal level (2.5 mg/l) showed stunted growth.…”
Section: Resultsmentioning
confidence: 51%
“…Artemisia vulgaris is a herbaceous plant which grows up to a length of 2.5 m and has a width of 75 cm. It is characterized by an intense aroma that is readily released when the leaves are crushed [ 30 , 43 ], and a spicy taste [ 44 ]. The plant has a thick main root and many small, fibrous lateral roots.…”
Section: Botanical Characteristicsmentioning
confidence: 99%
“…It is an important aromatic medicinal species with pungent smell and sharp taste [95]. It has been used to cure epilepsy, depression, irratibility, stress and insomnia in folk remedies.…”
Section: Artemisia Vulgaris Linn (Mugwort)mentioning
confidence: 99%
“…Effects of various ratio and concentration of phytohormones was also tested for micro-propagation of A. vulgaris from shoot tips and it was observed that MS medium supplemented with BAP and KIN gave the best response. Successful in vitro plant regeneration was achieved using leaf [95] and encapsulated somatic embryos as explants [111]. Artemisinin, a potent anti-malarial compound (2014), successfully regenerated this important medicinal plant in vitro using axillary buds as explants.…”
Section: Artemisia Species Conservationmentioning
confidence: 99%